Effect of MnOx phase on Pt-based catalyst for enhancing CO/C3H6/NO oxidation performance. (19th August 2022) - Liang, Yanli; He, Darong; Ding, Xinmei; Wang, Jianli; Zhao, Ming; Chen, Yaoqiang
Abstract: To improve the fuel economy, it is crucial to promote the low-temperature performance in eliminating diesel emissions. The work investigates the impact of different MnO2 /Mn2 O3 phase ratio on the low-temperature performance of Pt-based monolithic diesel oxidation catalyst. Near equal ratio of MnOx phase could form the three-phase (platinum, MnO2, Mn2 O3 ) interfacial structure, leading to the smaller platinum particle size and exhibiting the higher interface rate (1.6–11.1 times) than other mono-manganese oxide with platinum. Besides, the higher oxygen mobility and more active oxygen species could be contributed to the positive effect of Pt/MnOx interface, which are prevalent to activate the reactant and greatly enhance the TOF value (1.4–20.8 times). The results imply that the modification of multi-phase metal/oxide interface is potential in dispersing platinum for greatly enhancing the catalytic efficiency. Graphical abstract: Catalyst with near equal ratio of MnOx phase could promote the formation of three phases interface structure, which has a relative higher interface rate and TOF value for the oxidation reaction, indicating the excellent low-temperature performance. Image 1 Highlights: Equal ratio of MnOx phase on catalysts form the three phases interface structure. Catalyst with multi-interfacial structure has a relative higher interface rate. Multi-interfacial structure improves the platinum dispersion and TOF value. The low temperature oxidation performance was improved via controlling MnOx phase.